Research and implementation of data security for mobile terminal based on TEE - Shuzhen CHEN; Minwei YANG; Yao HE (Dianxin kexue)
The three kinds of data security scheme for mobile terminal were analyzed and compared. The framework of data security for mobile terminal based on TEE was proposed, and the typical mobile payment scheme based on TEE was discussed. On the basis of the typical scheme, an innovative business plan based on TEE to adjust the payment amount of fingerprintsdynamically was proposed, and finally the core code was given.